Politik Hukum Pemerintah Indonesia Tentang Perwakafan: Tarik Ulur Kepentingan - Hidayat, Rahmat; Tiswarni, Tiswarni (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
This research explains how the government legal politics in the field of waqf with the tug-of-war of various interests that influence this, both the interests of the government, society and the waqf law itself. To achieve this goal the author uses library research, where the data sources were obtained from books and articles that were offended by the topics discussed. Data was sorted out and analyzed using content analysis. This study found that the government legal politics regarding waqf can be seen from the condition of the government's relationship with Muslims. When the government's relationship with Muslims is tenuous, then the rule of Islamic law "appears to be slow and stagnant". On the other hand, if the relationship was harmonious, the rules of Islamic law, especially waqf, will develop. This is evidenced that since the Dutch colonization until the Old Order, the rules regarding waqf seemed to "stay in place". In other words, waqf regulations only regulate existing waqf practices, without any improvement in terms of both legal substance and utilization. The new waqf rules appeared in the second half of the New Order era and reached their peak during the Reformation period. Government legal politics regarding waqf is influenced by the interests of government and society on the one hand, where waqf can help improve people's welfare. On the other hand, Islamic law, especially waqf law, is growing in Indonesia through various emerging regulations.